Substance abuse and violence behavior - Habil, M.H.; Abd Rashid, R.; Sulaiman, A.H.; Peters, H.; Ahmad Zahari, M.M.; Amer Nordin, A.S.; Zakaria, H.; Robson, N.; Said, M.A.; Ahmad Adham, A. (2010)
Objectives: This paper examines the relationship of various licit/illicit substances and their association with violent behaviors. Methodology: The selection of related articles was searched via various database including google scholar, ovid and sciencedirect search engines. Results: Most of the literatures suggest presence of association of various substance use with violent behavior but no definite causal relationship between them. Conclusion: Further study is needed to determine the extended relationship in between substance use and violence.